Psycho-Sociocultural Determinants Of Cervical Cancer: Attitudes Towards The Human Papillomavirus Vaccine In Peru (The Review of Diabetic Studies, 2025)
Previous research has shown that cervical cancer is one of the main causes of death among women worldwide; despite this, significant percentages of the target population have shown attitudes of rejection towards the human papillomavirus vaccine. In this context, the objective of the study is to determine the degree of correlation between psycho-sociocultural factors and the attitude of parents of children towards the human papillomavirus vaccine. The research method is quantitative, non-experimental design, cross-sectional cohort, whose level of depth is descriptive-correlational; the sample is 99 parents of children who were in the fourth grade of primary education in a Public Educational Institution in the province of Yunguyo, in Puno, Peru; and an ad hoc Likert scale questionnaire was applied, with 25 items distributed among the studied variables. The results show that psycho-sociocultural factors are directly and strongly correlated with the attitude of parents (p-value=0.000, being < α=0.01); furthermore, both variables have a very high degree of negative correlation (r=-0.888). Therefore, psycho-sociocultural factors are determinants of the negative attitude of parents towards the human papillomavirus vaccine, so cervical cancer tends to be a perennial public health problem.